Analisis Pemeringkatan Bintang Jalan Akses Pasar Keputran Kota Surabaya - Vicky Kheir Riva; Nurani Hartatik; Mochamad Firmansyah (KOLONI, 2026)
Major cities in Indonesia face various challenges in public services, particularly in the transportation sector, where traffic congestion has become an increasingly complex issue. Surabaya, as one of the metropolitan cities with a population of 2,893,698, has experienced a significant increase in the number of motor vehicles, reaching more than 4 million units in 2022. This condition has contributed to the decline in road network performance, especially in areas with high economic activity such as Pasar Keputran. This traditional market serves as a major distribution center for vegetables and food commodities, with intensive activities occurring both during the day and at night. The main problems identified include illegal parking, limited parking facilities, loading and unloading activities on the roadway, and inadequate road width. These factors disrupt traffic flow, reduce the level of service of the roads, and increase the risk of traffic accidents. This study aims to analyze the functional feasibility and service quality of road segments providing access to Pasar Keputran based on the criteria outlined in the Regulation of the Minister of Public Works and Housing No. 4 of 2023 concerning Road Functional Feasibility Guidelines. The method used is the Star Rating Score (SRS), which considers safety aspects, geometric and physical road conditions, land use, and traffic flow characteristics. Data were collected through field observations and technical assessments in accordance with applicable standards. The results of this study are expected to provide a basis for local governments in formulating traffic management policies, optimizing road functions, and improving safety as well as the quality of public services in the Pasar Keputran area of Surabaya in a sustainable manner.